INFLUENCE OF FINE-DISPERSED BORON CARBIDE ON THE STRUCTURE AND CHARACTERISTICS OF IRON-BORON ALLOY - N. F. Nevar (Литьë и металлургия)
The influence of boron carbide as fine-dispersed material input into the melt on structure morphology, founding, technological and exploitation characterisstics of cast iron-boron material is shown.